Understanding satisfaction of airport user towards facilities: a case in Kuala Lumpur International Airport 2 (KLIA 2) - Alvin, Oh Shi Kai; Graceshealda, Rechard; Mohd Drus, Maysarah (2015)
Satisfactions are very important towards any kind of institutions. In this research, Kuala Lumpur International Airport 2 (KLIA2) has been chosen because it is new airport and researchers want to understand the level of satisfaction of airport users towards facilities that provided. Since it is new airport, for surely there are some facilities need to have improvements. Researchers highlighted facilities that provided by airport for this research are; dining and shopping, washroom, prayer room and parking lot. To obtain the information and data from the respondents, researchers distributed a questionnaire which is by using quantitative method. Then, data analysed by using Spearmen Correlation, from result dining and shopping facilities, washroom facility, prayer room facility and parking lot facility has positive relationship with the satisfactions of airport user towards facilities. The significant of research is to determine all facilities that had been highlighted in the research and airport users’ satisfactions. Even though there was negative feedback from respondents, but it help management team to do improvement